The Role of Diagnostics of State of Catenary Poles in the Traffic Safety System - Bayanov I. N.; Badretdinov T. N.; Muminov S. S. (Research Parks Publishing LLC, 2023)
When operating railways, much attention is paid to the diagnosis of the contact suspension as an unserviceable part of the power supply system. The poles of contact lines are not given due attention, considering them invulnerable. The available means of diagnosing the contact lines do not fully meet the requirements of the operation of power supply devices due to the insufficient number of parameters to be determined, including the determination of the state of the poles. Also, the problematic part in the diagnostic system of the contact lines is the adequacy of the reflection by diagnostic means of the actual quality of the state of contact lines. Improving the quality of diagnostic tools for assessing the condition of the entire contact lines involves identifying potential risk areas, preventing or minimizing the risks of failures, preventing the occurrence of risks based on their systematic forecasting.